POLA PENYESUAIAN DIRI MANTAN ANGGOTA GAFATAR PASCA PEMULANGAN KE DAERAH ASAL - Muzni, Achmad Irfan; Haniwati, Dwi (ANFUSINA: Journal of Psychology, 2019)
Abstract The arson expulsion experienced by a former Gafatar member in Mempawah, West Kalimantan led the government to take steps by returning former Gafatar members to their respective areas of origin. On the other hand, the Majelis Ulama Indonesia (MUI) officially declared that Gafatar was a cult. Both of these can create resistance from the surrounding community when former Gafatar members return to their respective regions of origin. This is a challenge for former Gafatar members to be able to adjust to their environment. This study aims to determine the pattern of adjustment of former Gafatar members after repatriation to the area of origin. Using a type of qualitative descriptive research. Data retrieval method using observation and interviews in-depth research subjects and other individuals around them. The research subjects were 3 people. The analytical method used is descriptive qualitative analysis, namely by giving a review or interpretation of the data obtained so that it becomes more clear and meaningful. From the data analysis it was found that in adjusting, former Gafatar members tended to be more selective in choosing the topic of conversation with the surrounding community, trying to think from the perspective of others, trying to provide an alternative perspective on their environment, following what their environment wants, be more careful in interacting, tend to ignore negative responses from the environment, and stay in touch with other former Gafatar members.Keyword: Pattern of Self-Adjustment, Former Gafatar Member